(untitled) (Global Journal of Computer Science and Technology, 2022)
This article describes the pursuit model by the method of chasing a group of objects All objects participating in the pursuit model move at a constant modulo velocity The pursuing object moves along a certain trajectory and releases objects at specified intervals whose task is to overtake the target by the chase method A single target in turn is tasked to overtake the pursuer by the method of parallel convergence A detection area is formed for each pursuing object The detection area is formed by two beams The velocity vector of an object is the bisector of the angle formed by such rays If the target is in the detection area then the object begins the pursuit by the chase method If the target leaves the detection area then the object makes a uniform and rectilinear movement